2021
DOI: 10.3390/polysaccharides2020017
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Oxidation on Wood and Its Application in Pb2+ Removal from Contaminated Water

Abstract: Raw wood was subjected to sequential oxidation to produce 2,3,6-tricarboxycellulose (TCC) nanofibers with a high surficial charge of 1.14 mmol/g in the form of carboxylate groups. Three oxidation steps, including nitro-oxidation, periodate, and sodium chlorite oxidation, were successfully applied to generate TCC nanofibers from raw wood. The morphology of extracted TCC nanofibers measured using TEM and AFM indicated the average length, width, and thickness were in the range of 750 ± 110, 4.5 ± 1.8, and 1.23 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Morphology studies (performed by various methods: optical microscopy, SEM, TEM, AFM) have all confirmed the defibrillation of the substrate associated with the oxidation, and the subsequent improved dispersity of cellulose fibrils bearing single or multiple functionality (aldehyde and/or carboxylic groups) [ 137 , 146 , 163 , 164 , 165 ]. For example, TEMPO-oxidized cellulose exhibited a web-like structure made of well-separated and randomly entangled fibers, evidenced by TEM [ 166 , 167 ]. The higher was the content in carboxylic groups, the smaller were the fibrils dimensions (nanometric scale).…”
Section: Environmental Applications Of Materials Based On Selectively...mentioning
confidence: 99%
See 1 more Smart Citation
“…Morphology studies (performed by various methods: optical microscopy, SEM, TEM, AFM) have all confirmed the defibrillation of the substrate associated with the oxidation, and the subsequent improved dispersity of cellulose fibrils bearing single or multiple functionality (aldehyde and/or carboxylic groups) [ 137 , 146 , 163 , 164 , 165 ]. For example, TEMPO-oxidized cellulose exhibited a web-like structure made of well-separated and randomly entangled fibers, evidenced by TEM [ 166 , 167 ]. The higher was the content in carboxylic groups, the smaller were the fibrils dimensions (nanometric scale).…”
Section: Environmental Applications Of Materials Based On Selectively...mentioning
confidence: 99%
“…One particular experimental approach has been studied in order to be applied for Pb(II) removal. Sequential oxidation of raw wood cellulose by a complex three-stage procedure (TEMPO-periodate-chlorite) has yielded in a cellulose derivative bearing three carboxylate groups (TCC) [ 167 ]. The sorbent material was able to retain high amounts of Pb(II) onto its surface (1569 mg/g), second only to nitro-oxidized cellulose nanofibers (their adsorption capacity of lead was 2270 mg/g), which is much less common for lead than for other heavy metals.…”
Section: Environmental Applications Of Materials Based On Selectively...mentioning
confidence: 99%
“…Many novel alumina, rare earth elements, and silica-gel based adsorbents have been determined to have high adsorption capacities for fluoride, but most of these are too expensive to be widely used [3]. Nanocellulose prepared from cost-effective method such as the nitro-oxidation method, is also known as an excellent adsorbent for water purification [4][5][6][7][8][9][10][11][12][13][14][15][16]. The World Health Organization (WHO) also claims excess fluoride removal is expensive and that the best method is to just find safe water, but that is often not possible.…”
Section: Introductionmentioning
confidence: 99%